NLRP3 Inflammasome Activation of Mast Cells by Estrogen via the Nuclear-Initiated Signaling Pathway Contributes to the Development of Endometriosis - Guo, Xinyue; Xu, Xinxin; Li, Tiantian; Yu, Qin; Wang, Jianzhang; Chen, Yichen; Ding, Shaojie; Zhu, Libo; Zou, Gen; Zhang, Xinmei (Frontiers in Immunology, 2021)
Endometriosis is an estrogen-dependent gynecological disease. The pathogenesis of endometriosis remains controversial, although it is generally accepted that the inflammatory immune response plays a crucial role in this process. Mast cells (MCs) are multifunctional innate immune cells that accumulate in endometriotic lesions. However, the molecular mechanism by which estrogen modulates MCs in the development of endometriosis is not well understood. Here we report that estrogen can induce the expression of NOD-like receptor family pyrin domain containing 3 (NLRP3) through estrogen receptor (ER)-α via the estrogen responsive element (ERE) in MCs. Such transcriptional regulation is necessary for the activation of NLRP3 inflammasome and the production of mature interleukin (IL)-1β in MCs. Targeted inhibition of NLRP3 significantly restrained lesion progression and fibrogenesis in a mouse model of endometriosis. Collectively, these findings suggest that MCs contribute to the development of endometriosis through NLRP3 inflammasome activation mediated by nuclear-initiated estrogen signaling pathway.